The effectiveness of the learning models and students’ critical thinking skills on mathematics learning outcomes in tangent lines to a circle - Ropang, Marlita; Mustamin Idris (Desimal: Jurnal Matematika, 2025)
Discovery learning was a learning model that encouraged students to actively construct their own knowledge, while critical thinking skills were essential for analyzing, reasoning, and solving mathematical problems. This study aimed to (1) determine whether there was a difference in mathematics learning outcomes between students taught using the discovery learning model and those taught using a conventional learning model and (2) determine whether there was a difference in mathematics learning outcomes between students with high and low critical thinking skills. The results showed that: (1) the discovery learning model was more effective than the conventional model in improving students’ mathematics learning outcomes (p = 0.019 < 0.05); (2) critical thinking skills had a significant effect on students’ mathematics learning outcomes (p = 0.040 < 0.05); (3) the combination of discovery learning and critical thinking skills provided better effectiveness, as students with both high and low critical thinking skills in the experimental class achieved relatively higher learning outcomes compared to those in the control class.